2021
DOI: 10.3389/feart.2021.712415
|View full text |Cite
|
Sign up to set email alerts
|

Deglacial Land-Ocean Linkages at the Alaskan Continental Margin in the Bering Sea

Abstract: A marine sediment record from the central Bering Sea, spanning the last 20 thousand years (ka), was studied to unravel the depositional history with regard to terrigenous sediment supply and biogenic sedimentation. Methodic approaches comprised the inference of accumulation rates of siliciclastic and biogenic components, grain-size analysis, and (clay) mineralogy, as well as paleoclimatic modelling. Changes in the depositional history provides insight into land-ocean linkages of paleoenvironmental changes. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…2). Wang et al (2021) found that the Alaskan mountain glaciers and Laurentide and Cordilleran ice sheets reached their maximum extent from 20 to 16.5 ka, suggesting permafrost of the Yukon basin may not have begun to be remobilized during this time. The Yukon River discharge did not increase until 16.5 ka (Wang et al, 2021), and the terrigenous OM transported by surface runoff thus may not have increased at ∼ 17.5 ka.…”
Section: Terrigenous Om Mobilization During the Last Deglaciationmentioning
confidence: 98%
See 3 more Smart Citations
“…2). Wang et al (2021) found that the Alaskan mountain glaciers and Laurentide and Cordilleran ice sheets reached their maximum extent from 20 to 16.5 ka, suggesting permafrost of the Yukon basin may not have begun to be remobilized during this time. The Yukon River discharge did not increase until 16.5 ka (Wang et al, 2021), and the terrigenous OM transported by surface runoff thus may not have increased at ∼ 17.5 ka.…”
Section: Terrigenous Om Mobilization During the Last Deglaciationmentioning
confidence: 98%
“…Wang et al (2021) found that the Alaskan mountain glaciers and Laurentide and Cordilleran ice sheets reached their maximum extent from 20 to 16.5 ka, suggesting permafrost of the Yukon basin may not have begun to be remobilized during this time. The Yukon River discharge did not increase until 16.5 ka (Wang et al, 2021), and the terrigenous OM transported by surface runoff thus may not have increased at ∼ 17.5 ka. Keskitalo et al (2017) found that the OM flux accumulated on the East Siberian Shelf during the PB-Holocene transition was high, and this OM was characterized by high S/V (0.28-0.90; mean value is 0.50) and C/V values (0.19-0.60; mean value is 0.35) (Fig.…”
Section: Terrigenous Om Mobilization During the Last Deglaciationmentioning
confidence: 98%
See 2 more Smart Citations
“…Driftwood derived from a source (pine, alder) in the southern NW Pacific may have been available after 16 ka [96]. Perhaps cold HE 1, which began approximately 17 ka, was a catalyst for a shift to a marine diet at a time when terrestrial resources would have declined, while accelerated glacial run-off from eastern Beringia is thought to have fertilized waters on the southern coast [97].…”
Section: The Settlement Of Beringiamentioning
confidence: 99%